Analisis Demam Berdarah Dengue (DBD) pada Remaja - Nelly Musyida; Jasmaniar Jasmaniar; Marniati Marniati (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Dengue Hemorrhagic Fever (DHF) is one of the endemic diseases that is still a public health challenge in Indonesia. Although the government has launched various programs, such as 3M Plus and fogging, the number of DHF cases still shows significant variations each year. This study aims to evaluate the community's contribution to controlling DHF by emphasizing the extent to which awareness is applied in real action. The method used is a literature study of 30 scientific articles on DHF published between 2015 and 2024. The results of the analysis show that although adolescents' knowledge of DHF is quite good, the implementation of preventive measures such as cleaning the environment, draining water reservoirs, and eradicating mosquito nests has not been carried out consistently. Several inhibiting factors include low community participation, lack of environmental supervision, and limited support from local governments. Therefore, a more comprehensive approach is needed, including ongoing education, strengthening the role of health cadres, and community-based supervision to increase the effectiveness of DHF control efforts.